A discussion on the relationship of Capila omeia (Leech, 1894) and C. pseudomeia Fan & Wang, 2004 syn. n. (Hesperiidae, Pyrginae) - Xue, Guoxi; Li, Meng; Rao, Zhi; Qiao, Yuemei (Zootaxa, 2023)
Intraspecific variability of Capila omeia (Leech, 1894) from Chongqing is investigated based upon the comparison of the 658 bp COI gene sequences and adult morphology. The morphological characters used for distinguishing C. pseudomeia Fan & Wang, 2004 from C. omeia are proved to be in the range of individual variation of the latter. Therefore, C. pseudomeia syn. n. is treated as a junior subjective synonym of C. omeia. Adults and genitalia of both sexes of C. omeia are illustrated. A distribution map of the species is provided as well.